Análise do processo de gestão de sistema de transporte público coletivo de regiões metropolitanas: estudo dos casos de Recife e Belo Horizonte - Aneliza de Souza Braga (2014)
The Metropolitan Area of Belo Horizonte (RMBH) has faced several challenges because of inadequate integration of its public passenger transport systems (PPTS) at the municipal and metropolitan levels. Overlapped transportation routes and poor services provided to users have implied delays and poor quality in the RMBH public transport system. Against this background, this thesis addresses issues of transportation management at the metropolitan level and provides a set of recommendations applicable to the RMBH. To approach the Metropolitan Area of Belo Horizonte, it relies on a review of the literature and a study of best practices in metropolitan areas in Brazil and abroad that could be used as a baseline. This study pointed to the Metropolitan Area of Recife as a national reference for proposing improvements in public transportation management in the RMBH. Two other metropolitan areas were selected as international references building on the following criteria: institutionally different areas compared to the RMBH, larger and more populated areas than the RMBH, and successful experiences of passenger mobility. The initial hypothesis was that establishing a transportation management consortium at the metropolitan level could solve the main problems experience in the RMBH. The results showed that the Metropolitan Area of Belo Horizonte urges a reformulated management model for its PPTS. It is crucial that the public managers either establish partnerships at the municipal and metropolitan levels or create a consortium to carry out an integrated management at the metropolitan level but also having some influence at the municipal level. The main contribution of this study is the comparative analysis of different transportation systems developed in different metropolitan areas, focusing on their management, identifying common and diverging trends, and highlighting successful areas that adopted the consortium model to manage transportation at the metropolitan level. The study also contributes particularly to heterogeneous metropolitan areas, as is the case of the RMBH, because it points out the feasibility of developing an integrated or even a single PPTS that meets the needs of the metropolitan inhabitants, provides the users with different transportation modes and adapts to the different traffic and demand conditions.